2006
DOI: 10.1111/j.1744-6171.2006.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Continuing Nursing Education Program in Child Psychiatry

Abstract: In a country that does not offer degree programs that integrate psychiatric nursing into the curriculum, CNE programs are an important educational option for nurses. The CNE program offered in this study, comprising lectures, discussion, interactive sessions, and case demonstrations totaling 60 hr across 10 days, was effective in improving the level of knowledge of nurses. It was equally beneficial for senior as well as less experienced nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…The results of our study are in line with other studies about participation in continuing education, which indicate a significant correlation between personal and professional factors and motivational orientations on the one hand and participation in continuing education on the other (3)(4)(5)(6)(7)(8)(9)(10) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of our study are in line with other studies about participation in continuing education, which indicate a significant correlation between personal and professional factors and motivational orientations on the one hand and participation in continuing education on the other (3)(4)(5)(6)(7)(8)(9)(10) .…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, properly training professionals have demonstrated high productivity, less occupational accidents or errors, a better organizational climate, work satisfaction and better patient results (5)(6)(7)(8) .…”
Section: Participation In Continuing Educationmentioning
confidence: 99%
“…Además, se ha visto alta productividad de los empleados entrenados apropiadamente, menor tasa de accidentes o errores de trabajo, mejor clima organizacional, satisfacción en el trabajo y mejores resultados del paciente. (3) Sin embargo en muchas ocasiones la práctica de la EC se encuentra disociada de la cotidianidad: las necesidades de los trabajadores son poco consideradas y se llevan a cabo programas de entrenamiento cuyos resultados son evaluados cuantitativa y no cualitativamente. Si como lo indican las investigaciones actuales, la EC contribuye a la práctica de calidad en la atención de enfermería, entonces las razones que influyen en su participación adquieren mayor significancia para la profesión de enfermería.…”
Section: Introductionunclassified
“…Indeed, a number of studies have demonstrated that there exists links between having access to CPD and staff satisfaction (Shields and Ward, 2001), with opportunities for CPD leading to staff retention. Other studies have also highlighted that CPD has the potential for increasing productivity, reducing accidents and errors in the delivery of healthcare, creating a better work environment and increasing job satisfaction (Chakraborty et al, 2006;Marzuki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%